2019
DOI: 10.1017/s0144686x19001016
|View full text |Cite
|
Sign up to set email alerts
|

Ageing, old age and older adults: a social media analysis of dominant topics and discourses

Abstract: Whilst representations of old age and older people in traditional media have been well documented, examinations of such representations within social media discourse are still scarce. This is an unfortunate omission because of the importance of social media for communication in contemporary society. In this study, we combine content analysis and discourse analysis to explore patterns of representation on Twitter around the terms ageing, old age, older people and elderly with a sample of 1,200 tweets. Our analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 93 publications
(100 reference statements)
3
31
0
1
Order By: Relevance
“…Media have long been acknowledged as a powerful vehicle for cultural beliefs about ageing (Miller et al 2015;Fraser et al 2016;Makita et al 2019). While older people tend to be under-represented in media coverage, when present they are typically framed in relation to a range of stereotypes (Loos and Ivan 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Media have long been acknowledged as a powerful vehicle for cultural beliefs about ageing (Miller et al 2015;Fraser et al 2016;Makita et al 2019). While older people tend to be under-represented in media coverage, when present they are typically framed in relation to a range of stereotypes (Loos and Ivan 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These representations can promote resentment by supporting an 'intergenerational warfare' frame that presents older people as a burden on younger, economically engaged individuals (Rozanova et al 2006). There is also a tendency to misrepresent older people as a homogeneous group (Loos and Ivan 2018;Makita et al 2019). These stereotypes not only conflate a culturally, ethnically, socioeconomically and geographically diverse segment of the population, but also ignore older people's agency and ability to promote and sustain social connections and manage other aspects of health and wellbeing (Wiles and Jayasinha 2013;Morgan et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For the past four decades, researchers have studied the global media depiction of older adults 1 and have found that the older population is typically underrepresented and portrayed negatively in Western cultures (1)(2)(3)(4)(5)(6)(7)(8). Worldwide, older adults are described as part of a homogeneous and vulnerable group and aging is mainly discussed in terms of significant economic and demographic problems (the expression of the "gray tsunami" is one of many examples expressing these "problems") (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that social media has become omnipresent in public life, representations of older people in such media have remained insufficiently studied (Makita et al, 2021). Among the existing and limited studies exploring social media representations of older people, they were found to be predominantly represented on Twitter as a disempowered, dependent, frail and homogeneous group (see Jimenez-Sotomayor et al, 2020;Makita et al, 2019;Meisner, 2020;Soto-Perezde-Celis, 2020).…”
Section: Social Media Adds Complexity To Representations Of Older Peoplementioning
confidence: 99%
“…positive light in entertainment media. However, social media representations of older people have remained insufficiently studied (Makita et al, 2021).…”
Section: Chapter 1: Introductionmentioning
confidence: 99%